Effects of high-pressure homogenization extraction on the physicochemical properties and antioxidant activity of large-leaf yellow tea polysaccharide conjugates. (November 2022) - Zhou, Cancan; Huang, Yuzhe; Chen, Jielin; Chen, Hao; Wu, Qianzhen; Zhang, Kunfeng; Li, Daxiang; Li, Yong; Chen, Yan
Abstract: This paper, discussed the high-pressure homogenization (HPH) method for the preparation of large-leaf yellow tea polysaccharide conjugates (LYTP), and the effects of LYTP on physicochemical properties as well as antioxidant activity were investigated. The results show that HPH extraction time was less than 0.5 h, and extraction rate reached 15.4%, which was nearly 1.8 times faster than that of hot water extraction (HWE). Component analysis showed that the total polysaccharide content of LYTP was higher, while the contents of polyphenols and free protein were lower than those of HWE. It is noteworthy that the 9.1% free protein content at 40 MPa was lower than that of the Sevag method (11.2%), indicating that HPH can eliminate the cumbersome protein removal process and is more environmentally. The small-molecule polysaccharide content extracted by HPH increased, but the monosaccharide composition did not change. Meanwhile, HPH decreased the particle size of the polysaccharides, and the changes in the surface topography of LYTP upon homogenization were confirmed with scanning electron microscopy. As a consequence, HPH extraction can improve the antioxidant capacity of LYTP. HPH extraction is an efficient, rapid and environmentally method for the preparation of polysaccharides, which could be widely used in the food industry. Graphical Abstract: ga1 Highlights: High-pressure homogenization extraction of polysaccharide from large-leaf yellow tea. This non-heating method is efficient, and can greatly shorten the extraction time. The physicochemical properties of the tea polysaccharides were determined and compared. The polysaccharides exhibited stronger antioxidant activities in vitro.